Efektifitas Program Rehabilitasi Berdasarkan Undang-Undang Nomor 35 Tahun 2009 Tentang Program Rehabilitasi Pencandu Narkotika Dan Psikotropika (Studi Kasus Yayasan Karunia Insani Cab Musirawas) - Handika Kartini Jefadalena; Wawan Fransico; Devi Anggreni Sy; Ahmad Fuadi (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
Narcotics and psychotropic abuse is a serious problem that threatens the younger generation and social stability in Indonesia. Data from the National Narcotics Agency (BNN) shows that the number of drug abusers continues to increase every year, from students, students, to productive workers. The negative impact of this coverage is not only felt by the users themselves, but also by their families, social environments, and even the state. Normative-empirical (applied) legal research is research that examines the implementation of positive legal provisions (legislation) and written documents in action (factual) in every specific legal event that occurs in society.The study aims to ensure whether the results of the application of law in legal events in concreto are in accordance with the provisions of laws and regulations. "Effectiveness of Rehabilitation for Narcotics Addicts as an Effort to Minimize Narcotics Crimes" (Himatul Aliyah. & Andri Wijaya Implement. Law Number 35 of 2009 Concerning Narcotics,Article 54 C. Improving Inter-Agency Cooperation: There is a need for increased collaboration between the Lubuklinggau City Police, the Lubuklinggau City Narcotics Agency, and Musirawas regarding rehabilitation programs and efforts by various related institutions, such as the City Government, social institutions, and community organizations. This synergy is crucial for expanding the network of drug abuse reduction efforts in the Musirawas area and accelerating their recovery process.oncerning Rehabilitation Programs. Keywords: Rehabilitation, Law, Narcotics   Abstrak Penyalahgunaan narkotika dan psikotropika merupakan salah satu permasalahan serius yang mengancam generasi muda dan stabilitas sosial di Indonesia. Data Badan Narkotika Nasional (BNN) menunjukkan bahwa jumlah penyalahguna narkoba terus mengalami peningkatan setiap tahunnya, baik dari kalangan pelajar, mahasiswa, hingga pekerja produktif. Dampak buruk dari penyalahgunaan ini tidak hanya dirasakan oleh pengguna itu sendiri, namun juga keluarga, lingkungan sosial, hingga negaraPenelitian hukum normatif-empiris (terapan), merupakan penelitian yang mengkaji pelaksanaan atau implementasi ketentuan hukum positif (perundang- undangan) dan dokumen tertulis secara in action (faktual) pada suatu setiap peristiwa hukum tertentu yang terjadi dalam masyarakat. Pengkajian tersebut bertujuan untuk memastikan apakah hasil penerapan hukum pada peristiwa hukum in concreto sesuai atau tidak sesuai dengan ketentuan peraturan perundang- undangan.“efektifitas rehablitasi bagi pencandu narkotika sebagai upaya meminimalisir tindak pidana narkotika”(himatul aliyah.& andri wijaya laksana. Undang -undang Nomor 35 Tahun 2009 Tentang Narkotika, Pasal 54 Tentang Program Rehabilitasi.Peningkatan Kerjasama Antarlembaga Perlu adanya peningkatan kerjasama antara Polres Kota Lubuklinggau, Badan Narkotika kota Lubuklinggau maupun di Musirawas megenai program atau upaya per rehabilitasi berbagai lembaga terkait, seperti Pemkot, lembaga sosial, dan organisasi masyarakat. Sinergi ini sangat penting untuk memperluas jaringan pengurangan pelaku penyalahgunaan narkotika di kawasan musirawas dan mempercepat proses pemulihan mereka. Kata kunci: Rehabilitasi, Undang-undang, Narkotika